Potensi Tepung Keong Terfermentasi sebagai Subtitusi Pakan Ternak dalam Meningkatkan Produksi dan Kualitas Telur Unggas - Ardiana Ayu Anjarwati (Universitas Sebelas Maret, 2021)
Poultry is a livestock commodity that is in great demand by many people. However, poultry egg production often declines and does not provide maximum results for farmers due to molting, and several other environmental factors. The use of high protein ingredients is known to increase the length of the reproductive tract of poultry, which is associated with an increased amount of egg production. Snail meat which contains a lot of protein can be used as animal feed. Based on this description, it can be predicted that snail meat can be used toimprove the decline in poultry egg production due to environmental influence. The performance of the snail meat content is improved by fermentation technology with lactic acid bacteria that are naturally found in aquatic animals.